Review response: Anastasia G. Yangaki, Ceramics in Plain Sight: The Bacini of the Churches of Crete - Yangaki, Anastasia G. (Journal of Greek Archaeology, 2023)
Dr Pamela Armstrong has penned a brief and often positive review of the publication of the bacini material from the Regional Unit of Chania and I appreciate her presentation. Nevertheless, reviews more or less reflect the interests of the reviewer, leading in this case to the presentation of only some of the aspects of the publication. Mention is made of Chapters I-V, but little or none of VI to VIII, which include the interpretative ‘core’ of the book. Chapter VI (pp. 135-183) constitutes a synthetic approach to uncover the various aspects of bacini use. It investigates how best this practice is to be interpreted and a range of factors are put forward: as well as having decorative and functional aspects, these turn out to be mainly symbolic (pp. 157-171). Thus are promoted indirect messages on religious connotations, on the objects’ original owners and donors, on the ceramics’ role as channels linking the private and the public spheres, where they should be recognized as offerings, heirlooms or relics, and on the intercultural relations between Venice and Crete. Therefore, the question of why these otherwise secular everyday objects were embedded in the exterior of ecclesiastical monuments is provided with a range of possible responses, rather than remains with no explanation, as suggested in the review (p. 514). In addition, a method of interpretation is proposed here for the first time, visually presented in fig. 184 at p. 147, by which one might systematically test/verify the contemporaneity or not first of each bacini assemblage with its respective monument and then of each vessel with the rest of the same assemblage. Chapter VII (pp. 187-291) comprises the detailed catalogue of the whole material, presented by district/province in the Chania Regional Unit, followed by a short Chapter VIII, which briefly recapitulates the book’s main content.